Hydrothermal Production of H2 and Magnetite From Steel Slags: A Geo-Inspired Approach Based on Olivine Serpentinization - Brunet, Fabrice (Frontiers in Earth Science, 2019)
The interaction between ultramafic rocks and hot seawater at slow-spreading mid-oceanic ridges triggers hydrothermal redox reactions which are known to produce magnetite and H2 under appropriate pressure and temperature conditions. Steel slags share some common properties with ultramafic rocks. They are composed of anhydrous and refractory minerals formed at temperatures exceeding 1200°C and they contain ferrous iron in comparable amounts. Consequently, both types of materials, natural and anthropogenic, when submitted to hydrothermal conditions are prone to form magnetite and H2 according the simplified redox reaction: 3[FeO] + H2O => Fe3O4 + H2 (1) where [FeO] is the ferrous iron component of the corresponding material that can be present under different mineralogical forms. Since H2 and magnetite, Fe3O4, especially when occurring as nanomaterial, are two valuable products for new-technology applications, the hydrothermal treatment of steel slags can be seen as a way to valorize a by-product of the steel industry of which a few tenths of billion tons are produced yearly. The hydrothermal behavior of steel slags which arise from basic oxygen furnace (BOF) operations and that of olivine, (Mg,Fe)2SiO4, the main mineral constituent of abyssal peridotites, is described here based on literature data. The thermochemical characteristics of Reaction 1 are reviewed for both types of materials in the perspective of optimizing a process that would valorize BOF steel slags for the production of nanomagnetite (and high-purity H2). In particular the kinetics effect of temperature, pH and solution-to-solid mass ratio on the hydrothermal oxidation of wüstite (FeO), considered here as an analogue of ferrous-iron component of steel slags, is modeled. The possible role of additive (impurity) on the hydrothermal oxidation of wüstite though the catalysis of the water-splitting reaction is discussed. Finally, the lack of kinetics constraints on nanomagnetite growth under hydrothermal conditions in a wide range of pH is identified has a major gap to understand two important issues, (1) the catalysis of abiotic molecules in the course of serpentinization reactions and (2) tailoring the size of the magnetite produced by hydrothermal treatment of BOF steel slags.